Response of Caligus rogercresseyi (Boxshall & Bravo, 2000) to treatment with Hydrogen Peroxide: Recovery of parasites, fish infestation and egg viability under experimental conditions. Issue 6 (17th September 2017) - Marín, S L; González, M P; Madariaga, S T; Mancilla, M; Mancilla, J
Abstract: Hydrogen peroxide (HP) is used to remove C. rogercresseyi from fish but little is known about its effect on this species. This study determined EC50 and concentration immobilizing 100% of specimens, capacity of parasites exposed to HP to recover and infest fish, and effect on survival into the copepodid stage. EC50 and concentration immobilizing 100% of specimens were estimated by exposing parasites for 20 min to 11 concentrations and evaluating effect at 1 and 24 h post‐exposure. Capacity to recover and infest fish, and survival into copepodid were evaluated by exposing parasites and eggs to HP for 20 min. Recovery and fish infestation were evaluated at 25 and 24 h post‐exposure, respectively. Eggs were grown until control reached the copepodid stage and survival calculated. EC50 was 709.8 ppm.100% immobilization was obtained at 825 ppm. Male and female recover 0.5 and 1 h post‐exposure, respectively. Percentage of parasites exposed and not exposed to HP that were recovered on fish was not significantly different. Survival to copepodid was lower in those exposed to HP. HP effect is greater on copepodids, but 100% of the mobile stages are immobilized under 825 ppm causing detachment from fish and potentially driven away, reducing infestation risk.